Inteligent Sentinel Agent - Correa, Eduardo Leiva (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2001)
The target of this text is present the project of a Software Agent capable of managing data received through the Internet. The paradigm of the agent is limited in a identification of unwanted subjects as pornography, occultism, drugs and so one specified by the supervisor. To execute this work, a Knowledge Base is created by means of words connected with the mentioned subjects. The decisions of the agent are supported by recognition of these words received through the Internet and later analysis with a decision tree. More details can be found at  www.inf.unisinos.br/pos-redes/seguranca/edicao3/isa/isa.html